Variety of Uniqueness and Messages Stored in The History of Toba Batak Traditional Houses - Irene Putri Simamora (An International Journal Tourism and Community Review, 2024)
Writing article This aim for describe one​ uniqueness culture in the Province​ North Sumatra ( North Sumatra ) to be precise Toba Batak tribe . The Toba Batak community has one characteristic typical area namely the unique Toba Batak House start from facet color , shape , style until meaning . Research on articles This use procedure study qualitative as qualitative refers to technique data collection in the form of stories , pictures , stories without contain numbers and values​​ mathematics and statistics . The Toba Batak House is House custom Toba Batak people who have meaning in each its shape and what it describes How variety values The noble who is in the house custom traditional the . that value own meaning as guidelines life in something association between individual . Toba Batak House only can found in Batak land and only the Toba people who own it , no can even found in other areas namely Karo Batak, Simalungun Batak , Pakpak Batak , and Mandailing Batak . The Toba Batak House is called public as House bolon , have Lots message stored in it in each part the building there is function utility to the meaning of the message contained in it , which makes it Toba people proud have one​ characteristic typical uniqueness area . Bolon which has big meaning This be one​ showing evidence​ that Toba Batak houses have big size .​